(untitled) (Research, Society and Development, 2022)
A breast fissure or nipple trauma is defined as a rupture of the epithelial tissue that extends through the nipple caused by inadequate grasping during suction. These traumas are very uncomfortable and painful, and can lead to the interruption of the breastfeeding process, leading to breast infection. The objective of this study is to report the experience in a health education activity with puerperal women who had difficulties in the breastfeeding process caused by breast fissures. This is a descriptive, qualitative research, of the experience report type, developed by nurses in a Municipal Health Unit, in the city of Ananindeua, based on an action to promote health education. In the course of the reports, six postpartum women, from a first pregnancy, reported that they were experiencing problems that are resulting in cracks in the breasts, and three other postpartum women commented that they had recently suffered from the same intercurrence. Thus, the other pregnant women who were in the room reported that they had already heard about the topic, but would not know how to resolve or mitigate them if they were to happen. In summary, the lack of information during prenatal care can revert the act of breastfeeding to a painful and ineffective process for the baby’s development and growth, resulting in nipple trauma such as cracks, due to incorrect suction, however, it is easy to solve, given that educational activities would likely be effective.